Macrokinetic Model of Catalase Electrode with Biphasic Enzyme Inhibition - Kriaučiūnas, K.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2004)
Macrokinetics of catalase based enzyme electrode was investigated in presence of enzyme inhibitor – hydroxylamine. The modeling of the electrode was performed using biphasic scheme of enzyme inhibition and external diffusion limitation. The maximal enzyme electrode sensitivity was indicated at transition from diffusion to kinetically controlled mode. The fitting of experimental data demonstrated that the enzyme electrode had 70% of maximal sensitivity
Keywords: enzyme electrode; catalase; Aspergillus niger; hydroxylamine; inhibition